2014
DOI: 10.1080/13658816.2014.953164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of landslide susceptibility mapping methods: a case study for the Ulus district, Bartın, northern Turkey

Abstract: The purpose of this study was to investigate the capabilities of different landslide susceptibility methods by comparing their results statistically and spatially to select the best method that portrays the susceptibility zones for the Ulus district of the Bartın province (northern Turkey). Susceptibility maps based on spatial regression (SR), linear discriminant analysis (LDA), quadratic discriminant analysis (QDA), logistic regression (LR) method, and artificial neural network method (ANN) were generated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Common practises involve the use of stochastic and/or data mining methods relying on presence/absence techniques (e.g., Eker et al, 2014;Ermini et al, 2005;Pourghasemi et al, 2013;Lombardo et al, 2014) for calibrating the predictive model. In this research we decided to pursue a presence-only approach, which has recently been introduced within the landslide scientific community (Convertino et al, 2013;Davis et Sims, 2013;Park, 2014) by applying the Maximum Entropy (MaxEnt) algorithm (Elith et al, 2011;Phillips et al, 2004 and2006;Phillips and Dudík, 2008), which does not rely on the contribution of negative (no-landslide or absence) cases for calibration.…”
Section: Introductionmentioning
confidence: 99%
“…Common practises involve the use of stochastic and/or data mining methods relying on presence/absence techniques (e.g., Eker et al, 2014;Ermini et al, 2005;Pourghasemi et al, 2013;Lombardo et al, 2014) for calibrating the predictive model. In this research we decided to pursue a presence-only approach, which has recently been introduced within the landslide scientific community (Convertino et al, 2013;Davis et Sims, 2013;Park, 2014) by applying the Maximum Entropy (MaxEnt) algorithm (Elith et al, 2011;Phillips et al, 2004 and2006;Phillips and Dudík, 2008), which does not rely on the contribution of negative (no-landslide or absence) cases for calibration.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yilmaz (2009) assessed landslide susceptibility with four methods (conditional probability, logistic regression, artificial neural network, and support vector machine) and concluded that the difference in the prediction accuracy of the four different methods was within 0.2%. Eker et al (2014) compared five methods for landslide susceptibility evaluation (linear discriminant analysis, quadratic discriminant analysis, artificial neural network, logistic regression, and spatial regression) and drew similar conclusions that the five different methods have a similar prediction accuracy with a largest difference of less than 0.5%. As the comparison analysis revealed, with the same data processing, there is little difference in the prediction accuracy between the above methods (Melchiorre et al 2008;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 83%
“…The majority of the variables used in the analysis were derived from the digital elevation models in order to analyse the sensitivity of LSZ maps. Information and database regarding the palaeoslide locations are considered as the most crucial information needed to generate the LSZ map of any area (Ayalew et al, 2004, Yilmaz, 2009, Pourghasemi et al, 2014, Regmi et al, 2014, Eker et al, 2015. In the present analysis, 52 landslide initiation locations were mapped from the field.…”
Section: Methodsmentioning
confidence: 99%